- Konten Hadis dalam Manuskrip Kitab Wawacan Panganten Tujuh - Maulana, Muhammad Falikh Rifqi; Raharusun, Agus Suyadi; Ahmed, Ismail Ibrahim el Sayed (Jurnal Lektur Keagamaan, 2024)
This study examines the integration of Sundanese culture and hadith teachings in the Wawacan Panganten Tujuh manuscript, an Islamic heritage of the archipelago with historical and spiritual significance. The research addresses the lack of academic studies exploring the cultural and religious dimensions of this manuscript. It aims to uncover the Islamic values within Wawacan Panganten Tujuh, particularly those referencing hadith, and to analyze the harmonization between local traditions and Islamic teachings. This study employed a qualitative approach, utilizing content analysis techniques and intertextuality theory, supported by philology, hadith takhrij, and Stuart Hall's theory of acceptance. The findings reveal that Wawacan Panganten Tujuh reflects the acculturation process between Sundanese culture and Islamic teachings through narrative elements, cultural symbolism, and marriage rituals such as huap lingkung and walimatul ursy, which align with the Sunnah of the Prophet (PBUH). These elements are adapted in a local context to reinforce the moral and spiritual message of marriage. In conclusion, this manuscript serves not only as a medium for preserving traditions but also as a relevant da'wah tool to address the challenges of modernization. With its profound Islamic values and contextual relevance, Wawacan Panganten Tujuh underscores the importance of maintaining harmony between local culture and Islamic sharia in building a unique Islamic identity in the archipelago.